FATIGUE PERFORMANCE ANALYSIS OF CASTING CRANES CONSIDERING NON⁃LINEAR CUMULATIVE DAMAGE - YAN MengYu; WEI GuoQian; DUAN RuoChen (Jixie qiangdu)
Aiming at the fatigue problem of casting cranes in service process,considering the actual service load spectrum,the fatigue performance of casting cranes was analyzed based on the non⁃linear cumulative damage principle.Firstly,the stress time history of the key fatigue hot spots of the in⁃service casting crane in a steel plant was measured.Then,the one⁃dimensional load spectrum was compiled based on the two⁃parameter rain flow counting method and Goodman equal life equation.In addition,the commonly used linear cumulative damage model and low⁃high and high⁃low non⁃linear cumulative damage model were used to calculate and analyze the damage and life characteristics of the key parts.The results show that the fatigue load spectrum of casting cranes is closely related to the location of fatigue calculation point and the actual service process.Compared with the commonly used linear cumulative damage model,the non⁃linear cumulative damage model has higher prediction accuracy,and more conservative life prediction results can be obtained by using the high⁃low load loading sequence.